Unpacking the Internal Sustainability Drivers for Enhanced Performance of Construction Firms - Rotimi, Funmilayo Ebun; Kalatehjaria, Roohollah; Moshood, Taofeeq Durojaye; Jalali, Zahra (MDPI AG, 2025)
Construction firms struggle to implement sustainable practices, delivering triple bottom line benefits despite growing environmental pressures. While research examines isolated sustainability drivers, the understanding of how organizational factors integrate to enable successful implementation remains fragmented. This systematic literature review synthesizes 249 articles (2010–2025) to develop an integrated framework explaining how internal capabilities drive sustainable innovation and performance in construction. This thematic synthesis reveals three critical insights. First, successful sustainability requires integrated configuration across green innovation capabilities, organizational learning, environmental governance responses, and performance measurement, not isolated initiatives. Second, construction’s project-based discontinuity, fragmented supply chains, and regulatory heterogeneity require capability configurations absent from manufacturing-focused sustainability theories. Third, cross-domain synergies create reinforcing feedback loops where capabilities enable compliance, measurement accelerates innovation, and governance catalyses development. This research provides practitioners an actionable framework identifying critical capability investments and interdependencies for sustainability implementation. Theoretically, we extend the Natural Resource-Based View and the Dynamic Capability View through three construction-specific mechanisms: temporal knowledge discontinuity paradox, distributed capability configuration, and regulatory complexity multipliers. These extensions advance sustainability theory beyond manufacturing, providing a foundation for understanding sustainable competitive advantage in project-based, fragmented industries.
Keywords: 33 Built Environment and Design; 12 Responsible Consumption and Production; 11 Sustainable Cities and Communities; 1201 Architecture; 1202 Building; 1203 Design Practice and Management; 3301 Architecture; 3302 Building; 4005 Civil engineering; sustainable innovation; green innovation; sustainable practices; construction performance